Laparoscopic distal resection of the pancreas. Can be all resections of body and tail of the pancreas called the same? - Šileikis, Audrius; Beiša, Augustas; Beiša, Virgilijus; Kvietkauskas, Mindaugas; Kryžauskas, Marius; Strupas, Kęstutis (Contemporary Oncology/Współczesna Onkologia, 2017)
Introduction: Distal resection of the pancreas is a routine procedure in high-volume centres. However, the volume of this procedure can vary. This variation plays a very important role in laparoscopic approach of pancreatic surgery and can be a real challenge if the anatomical situation is underestimated. Aim of the study : To present our experience in minimally invasive treatment of the pancreatic tumours and to discuss different approaches to different anatomical situations. Material and methods : We performed a retrospective analysis of patients, who underwent laparoscopic pancreas resection for pancreatic cancer in our hospital since 2014 to 2016 February. According to extension of operation, patients were divided into two groups: distal pancreatectomy and left hemipancreatectomy for cases that required preparation of the portal vein. Demographic characteristics, and operative and postoperative data were compared between both groups. Results : Out of 16 patients, distal pancreatectomy was performed for 7 (43.8%) and left hemipancreatectomy for 9 (56.2%) patients. For 1 (14.3%) laparoscopic distal pancreatectomy and for 2 (22.2%) laparoscopic left hemipancreatectomy patients surgical conversion to laparotomy was performed. The average operation time was 205 (195–245) min for distal pancreatectomy and 412.5 (280–520) min for left hemipancreatectomy group (p = 0.001), blood loss 125 (20–250) ml and 250 (50–1800) ml accordingly (p = 0.138). Totally postoperative fistula occurred in 7 (43.8%) cases; out of them, 5 (71.4%) patients were from the left hemipancreatectomy group. Conclusions : Laparoscopic left hemipancreatectomy is more complicated than distal pancreatectomy. Extension and technique selection of distal resection of the pancreas depends on the Yonsei criteria and tumour relation to the portal vein.